2015
DOI: 10.5194/acp-15-1105-2015
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between the scattering phase function of cirrus and the atmospheric state

Abstract: Abstract. This is the first paper to investigate the relationship between the shape of the scattering phase function of cirrus and the relative humidity with respect to ice (RH i ), using space-based solar radiometric angle-dependent measurements. The relationship between RH i and the complexity of ice crystals has been previously studied using data from aircraft field campaigns and laboratory cloud chambers. However, to the best of our knowledge, there have been no studies to date that explore this relationsh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 83 publications
3
13
0
Order By: Relevance
“…Thus, it is possible that the majority of cirrus clouds during the observation period in Munich contain a large fraction of rough ice crystals. This would support the hypothesis of Knap et al (2005), Baran and Labonnote (2006), and Baran et al (2015), who found that on average rough ice crystals better reproduce remote sensing radiance measurements than assuming crystals with smooth surface. However, if multiple scattering by cirrus clouds or aerosol is accounted for, the minimum fraction of smooth crystals could be much larger in the case of haloproducing cirrus clouds.…”
Section: Application Of the Halo Detection Algorithmsupporting
confidence: 77%
“…Thus, it is possible that the majority of cirrus clouds during the observation period in Munich contain a large fraction of rough ice crystals. This would support the hypothesis of Knap et al (2005), Baran and Labonnote (2006), and Baran et al (2015), who found that on average rough ice crystals better reproduce remote sensing radiance measurements than assuming crystals with smooth surface. However, if multiple scattering by cirrus clouds or aerosol is accounted for, the minimum fraction of smooth crystals could be much larger in the case of haloproducing cirrus clouds.…”
Section: Application Of the Halo Detection Algorithmsupporting
confidence: 77%
“…We think it more likely, however, that when faced with strongly non‐Weibull PDFs (such as the bimodal distribution appearing in Figure c), in situ retrieval algorithms compensate by assigning excessively low values of η W . In terms of scale parameters, our results span a similar range to that reported from the above in situ studies ( σ W up to ~0.25) but are small compared to the results of remote sensing studies ( σ W up to ~0.5) [ Cole et al ., ; van Diedenhoven et al ., ; Baran , ; Hioki et al ., ]. But our results are obtained under a rather narrow range of conditions, −39°C to −29°C and near‐equilibrium humidity, whereas remote sensing studies span a much larger range.…”
Section: Discussionmentioning
confidence: 99%
“…Cirrus clouds play an important role in the Earth's climate by absorbing and reflecting infrared and solar radiation [Stephens et al, 1990;Lynch, 2002;Baran, 2009Baran, , 2012van Diedenhoven et al, 2014b;Baran, 2015]. Although crystals making up these clouds possess complex geometries, a useful simplification is to consider them as aggregates of simpler components, especially hexagonal-shaped prisms.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetry parameter on the other hand is expected to be positively correlated with the HR (Ulanowski et al, 2006(Ulanowski et al, , 2014Gayet et al, 2011). Many studies (Korolev et al, 2000;Garrett et al, 2001;Baran and Labonnote, 2007;Shcherbakov et al, 2006;Gayet et al, 2011;Baum et al, 2011;Cole et al, 2013;Ulanowski et al, 2014;Baran et al, 2015) suggest that cirrus clouds are mainly formed by rough or complex particles giving rise to typically featureless SPFs, confirming indications from previous observations and explaining the relative rarity of ground-observed halo occurrences (Sassen et al, 1994). Nevertheless, recent findings (Forster et al, 2017) suggest that the fraction of halo-producing cirrus might be larger than previously thought.…”
Section: Introductionmentioning
confidence: 53%